Theoretical Study And Indoor Experimental Validation Of Performance Of The New Photovoltaic Thermal Solar Collector (PVT) Based Water System - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Sachit, Fadhil Abdulameer (Elsevier Ltd, 2020)
Hybrid Photovoltaic Thermal (PVT) systems are an solar technology that the enables simultaneous the conversion of solar energy into electrical and thermal energy. One of the major problems of photovoltaic plates PV is high temperature due to excessive solar radiation and high ambient temperature leads to reduced efficiency in solar panels. The hybrid photovoltaic thermal (PVT) systems are one of the most common methods for cooling photoelectric panels and improve performance. The heat from the PV panel is transferred through working fluids such as water. The extracted heat is used in low temperature applications, including household hot water. A new dual oscillating absorber copper pipe flow that was designed based on the water-based PVT system, was developed and studied. This paper discusses experimental data utilizing in the MATLAB program with indoor experimental studies of the water-based PVT system and compare the results of the new design dual oscillating absorber of the PVT water system with a normal PV panel without a cooling system. The simulation results were validated with experimental results. The simulation and experimental results were found to be in good agreement. The performances of the water-based PVT system that includes the electrical, thermal and total efficiency was measured in the solar radiation range from 500 to 1000 W/m2 and different mass flow rate from 2 to 6 LPM. The results show that the maximum electrical efficiency is 11.5% at 500 W/m2 and 6 LPM, the maximum thermal efficiency is 58.64% at 1000 W/m2 and 5 LPM, and the total efficiency is 66.87% at 1000 W/m2 and 5 LPM. The results show that increasing the mass flow rate and solar radiation leads to an increase in the thermal and total efficiency, but after the optimal value, the thermal and total efficiency decreases. The increasing mass flow rate lead to reduces the cell temperature and increases the electrical efficiency.